Impact of drug loading in mesoporous silica-amorphous formulations on the physical stability of drugs with high recrystallization tendency - Rayane S.C.M.Q. Antonino; Michael Ruggiero; Zihui Song; Thais Leite Nascimento; Eliana Martins Lima; Adam Bohr; Matthias Manne Knopp; Korbinian Löbmann (Elsevier, 2019)
In this study, a method is described to determine the monolayer loading capacity (MLC) of the drugs naproxen and ibuprofen, both having high recrystallization tendencies, in mesoporous silica (MS), a well known carrier that is able to stabilize the amorphous form of a drug. The stabilization has been suggested to be due to direct absorption of the drug molecules onto the MS surface, i.e. the drug monolayer. In addition, drug that is not in direct contact with MS surface can fill the pores up to its pore filling capacity (PFC) and is potentially stabilized by confinement due to the pore size being smaller than a crystal nuclei. For drugs with high recrystallization tendencies, any drug outside the pores crystallizes due to its poor physical stability. The drug monolayer does not contribute to the glass transition temperature (Tg) in the DSC, however, the confined amorphous drug above MLC has a Tg and the heat capacity (ΔCp) over the Tg increases with an increasing fraction of confined amorphous drug. Hence, several drug loading values above the MLC were investigated towards the presence of a Tg and ΔCp using differential scanning calorimetry (DSC). A linear correlation between the amount of confined amorphous drug and its ΔCp was identified for the mixtures between the MLC and PFC. By subsequent extrapolation to zero ΔCp the experimental MLC could be determined. Using theoretical density functional theory (DFT) and ab initio Molecular Dynamics (AIMD), the binding energies for the monolayer suggested that the monolayer in fact is thermodynamically more favorable than the crystalline form, whereas the confined amorphous form is thermodynamically less favorable. Consequently, a physical stability study showed that the confined amorphous drugs above the MLC were thermodynamically unstable and consequently flowing out of the pores in order to crystallize, whereas the monolayer remained physically stable. Keywords: Mesoporous silica, Loading capacity, Differential scanning calorimetry (DSC), Amorphous